China Xinjiang Province Workforce Development : SABER Country Report 2014 - World Bank (Washington, DC, 2014)
This report presents the findings of the assessment of the workforce development (WfD) system of Xinjiang Province, China, conducted based on the World Bank s Systems Approach for Better Education Results (SABER) WfD analytical framework and tool. The focus is on policies, institutions, and practices in three important functional dimensions of policymaking and implementation strategic framework, system oversight and service delivery.